EVALUASI PELAKSANAAN TANGGUNG JAWAB SOSIAL PT. ADIRA FINANCE DI KELURAHAN SATRIA KECAMATAN BINJAI KOTA KOTA BINJAI - Siregar, Barham (PERSPEKTIF, 2014)
Development, in addition to the positive impact also brought environmentaldisaster for many because the environment is considered as an object that connotescommodities and continue to be exploited without taking into account the carryingcapacity of the environment. One of the efforts to improve the environmentalbalance is through a program of Corporate Social Responsibility (CSR). CorporateSocial Responsibility (CSR) which is the formulation of research problems is theimplementation of the implementation of Corporate Social Responsibility (CSR) asthe social capital of PT. Adira Finance, how assessment Corporate PerformanceAssessment Program (PROPER) on Corporate Social Responsibility (CSR) PT.Adira Finance and favorable factors and inhibiting the implementation ofCorporate Social Responsibility (CSR) PT. Adira Finance.This type of research isdescriptive qualitative. Primary data were obtained from interviews andquestionnaires to the 40 members of the public and direct observation.Inimplementing CSR PT. Adira Finance has been working on the preservation of theenvironment, support environmental awareness programs. And for CSR activitiesconducted in the Village District Satria Binjai City PT. Adira Finance held areforestation program to plant 400 mahogany trees.